Model Bisnis Portal Media Online Lokal Suarantb.com - Paganini, Asmarani Pamela (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
In the midst of the increasingly complicated competition of mass media companies with the presence of digital native news requires Suara NTB Newspaper to continue to innovate in order to survive in an increasingly complex competitive ecosystem. Information consumption patterns have also changed along with the emergence of alternative sources of information on online media, encouraging Suara NTB to venture into digital media by launching Suarantb.com on July 8, 2016. With Suarantb.com, a new business model was designed by the editorial management to expand the reach of readers and gain revenue and economic benefits. How then the change in the business model change the work routine and workflow of the Suara NTB work team. This research uses qualitative methods through data collection techniques: interviews with the editorial crew of suarantb.com, direct observation of the suarantb.com online portal, and documentation in the form of archives and images related to the business model. The results showed that the business model applied by suarantb.com is in the form of offering e-paper subscription packages, advertising columns on websites and news articles, and news or advertorial advertisements. The suarantb.com advertising packages offered are also designed to be integrated with their social media.